Deregulation and regional specialization: Evidence from Canadian agriculture - Colin Andre Carter; Shon Ferguson (Research Institute of Industrial Economics (IFN), 2017)
For about seventy years, the Canadian Wheat Board (CWB) was one of the world's largest export "single desk" state traders in agriculture, until it was deregulated in 2012 and stripped of its marketing powers. One of the main crops controlled by the CWB was barley. We estimate the impact of the removal of the CWB's single desk on the spatial pattern of malting barley production in Western Canada. We find that deregulation encouraged growers located closer to malt barley plants to increase production relative to growers located further from the plants. Additionally, malting barley production shifted to regions with more of a natural advantage arising from climatic conditions. This change in cropping patterns after deregulation can be explained by efficiency gains, combined with transportation and handling cost savings.
Keywords: L43; Q17; Q18; R12; R14; 330; State trading; Deregulation; Agricultural regulation; Trade costs; Comparative advantage